Treatment of abdominal granuloma and hypercalcaemia caused by Cladophialophora bantiana with combination antifungal chemotherapy and hyperbaric oxygen therapy in a dog. Issue 2 (28th April 2020) - Lester, Mary; Walton, Stuart; Vilaplana Grosso, Federico; Shmalberg, Justin
Abstract : A 5‐year‐old intact male Boxer was evaluated for a 4‐month history of ventral abdominal mass with fistulous tracts. Thoracic and abdominal CT revealed a large soft‐tissue mass in the rectus abdominis muscle extending into the peritoneal cavity. Cytologic and histologic findings were consistent with an intra‐abdominal fungal granuloma with pigmented fungal hyphae suggestive of phaeohyphomycosis. PCR of the isolated fungal organism confirmed Cladophialophora bantiana as the aetiologic agent. Initial therapy consisted of oral terbutaline and itraconazole and weekly to biweekly hyperbaric oxygen therapy. Intralesional amphotericin B was initiated following diagnosis. Therapy was associated with transient draining tract resolution though the mass remained overall static in size. Hypercalcaemia with associated increased serum calcitriol developed with progressive disease, which resolved in response to low‐dose steroid therapy and a calcium‐restricted and vitamin D‐restricted diet. The dog was euthanised 13 months after initial presentation following the development of acute weakness, fever and dyspnoea.